THE YOUTH OF KAZAKHSTAN AND KYRGYZSTAN: COMPARATIVE ANALYSIS OF POLITICAL ACTIVISM - NASSIMOVA, Gulnar; KILYBAYEVA, Shugyla; SMAGULOV, Kadyrjan; BASYGARUYEVA, Zhuldyz (CENTRAL ASIA AND THE CAUCASUS, 2019)
Studies of youth political activism are highly topical because, first, political involvement is an inalienable part of the political system, social and political institutions, and the level of political culture. The political involvement of the younger generation determines, to a great extent, the efficiency of social, economic, and political reforms and the country’s future. Secondly, at the turn of the twenty-first century, young people played an especially prominent role in the protests that shook North African and Middle Eastern countries. These protests led to regime changes and the so-called color revolutions of the spring of 2011. In many countries, protest movements are used or misused by destructive radical forces. Thirdly, discussions of the nature and level of youth political activism pushed the problem to the forefront of political science. On the one hand, researchers note the low level of political activism of the younger generation, which looks apolitical and is gradually losing interest in politics. On the other hand, the forms of political activism are becoming more numerous and gradually acquiring new forms; information technologies play a new, previously unknown role and influence the political behavior of the younger generation to a much greater extent than before. This means that to identify and analyze the causes and factors that led to new forms and trends in youth political activism, we should rely on conceptual approaches and scholarly methods of study. We have selected Kazakhstan and Kyrgyzstan as the subjects of our studies because they are coping with more or less identical political problems and yet demonstrate certain peculiarities in the functioning of their political systems and methods of ensuring stability. We have identified the role of youth in political processes, its attitude toward current social, economic, and political events, and the ways in which the younger generation influences political decision-making in the corridors of power.